Th SYSTEMATIC REVIEW ON SYNTHETIC AND HERBAL MEDICATIONS FOR THE TREATMENT OF ALOPECIA - PRIYA BHAWARE; PADMAJA KORE (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Alopecia refers to the scientific word for diminished hair growth or balding. It describes a disease in which hairs falls off from one or more parts of your body, most commonly the scalp. Losing your hair might be triggered by a variety of factors, including hereditary traits, external factors, chemical exposure, medication, dietary insufficiency, chronic tension, or prolonged sickness, among others. Alopecia is categorized into different types depending upon its pattern of diminished hair growth and its genesis. The pursuit of effective treatments has led to the exploration of both synthetic and herbal medications. This study examines the performance, mechanisms of action, tolerability profiles, and limits of synthetic and herbal remedies for alopecia. Synthetic medications such as minoxidil and finasteride are commonly prescribed and have demonstrated varying degrees of success in clinical trials. However, concerns regarding adverse effects and long-term efficacy persist. Conversely, herbal medications, including saw palmetto, ginseng, and pumpkin seed oil, have gained popularity due to their perceived natural origin and potentially fewer side effects. Nevertheless, the scientific evidence supporting their efficacy remains limited and often inconclusive. Additionally, challenges in standardization and regulation pose significant barriers to the widespread adoption of herbal treatments. This study aims to provide healthcare professionals and patients with a comprehensive overview of the current landscape of synthetic and herbal medications for alopecia, highlighting the need for further research to elucidate their therapeutic potential and optimize patient outcomes.